Plasma catecholamine levels in the acute and subacute stages of takotsubo syndrome: Results from the Stockholm myocardial infarction with normal coronaries 2 study. Issue 11 (7th September 2021) - Y‐Hassan, Shams; Sörensson, Peder; Ekenbäck, Christina; Lundin, Magnus; Agewall, Stefan; Brolin, Elin Bacsovics; Caidahl, Kenneth; Cederlund, Kerstin; Collste, Olov; Daniel, Maria; Jensen, Jens; Hofman‐Bang, Claes; et al.
Abstract: Aims: It is well‐accepted that takotsubo syndrome (TS) is characterized by a massive surge of plasma catecholamines despite lack of solid evidence. The objective of this study was to examine the hypothesis of a massive catecholamine elevation in TS by studying plasma‐free catecholamine metabolites in patients participating in the Stockholm myocardial infarction (MI) with normal coronaries 2 (SMINC‐2) study where TS constituted more than one third of the patients. Methods and results: The patients included in the SMINC‐2 study were classified, according to cardiac magnetic resonance (CMR) imaging findings (148 patients), which was performed at a median of 3 days after hospital admission. Plasma‐free catecholamine metabolites; metanephrine, normetanephrine, and methoxy‐tyramine were measured on day 2–4 after admission. Catecholamine metabolite levels were available in 125 patients. One hundred and ten (88%) of the 125 patients included in SMINC‐2 study, and 38 (86.4%) of the 44 patients with TS had completely normal plasma metanephrine and normetanephrine levels. All patients had normal plasma methoxy‐tyramine levels. Fourteen (11.2%) of the 125 patients included in SMINC‐2 study, and 5 (11.6%) of the 43 patients with TS had mild elevations (approximately 1.2 times the upper normal limits) of either plasma metanephrine or normetanephrine. One patient with pheochromocytoma‐triggered TS had marked elevation of plasma metanephrine and mild elevation of plasma normetanephrine. There were no significant differences between the number or degree of catecholamine metabolite elevations between the different groups of patients with CMR imaging diagnosis included in SMINC‐2 study. Conclusion: There was no evidence of massive catecholamine elevations in the acute and subacute stages of TS apart from one patient with pheochromocytoma‐induced TS. Most of the TS patients had normal catecholamine metabolites indicating that blood‐borne catecholamines do not play a direct role in the pathogenesis of TS.